Feasibility of a new clinical journal club implementation and its association with knowledge, attitudes, and application of evidence-based practice among chiropractic students and trainees: a before-and-after healthcare education improvement study - Melanie Häusler; Rahim Lalji; Léonie Hofstetter; Cesar A. Hincapié (Chiropractic & Manual Therapies, 2023)
Abstract Background Evidence-based practice (EBP) is the integration of best research evidence with clinical expertise and patients’ values and preferences. Little is known about knowledge, attitudes, and application of EBP among chiropractic students and trainees. Our aims were to (1) examine the feasibility of implementing a new journal club format within a Swiss university chiropractic healthcare education setting, and (2) assess the associations between the new journal club implementation and EBP characteristics among chiropractic students. Methods A before-and-after study was conducted through a newly implemented journal club with 5th and 6th year chiropractic students and postgraduate trainees between 1 February 2021 and 31 July 2021. The journal club was developed based on the “community of practice” and “team-based learning” conceptual frameworks. EBP knowledge, attitudes, personal application, and future use, were assessed with a validated questionnaire. We summarised participant characteristics using descriptive statistics, estimated before-and-after EBP total and subscale scores (i.e., knowledge, attitudes, personal application, and future use), and conducted an exploratory subgroup analysis based on journal club attendance (Group A: 3–5 sessions attended; Group B: ≤ 2 sessions attended). Results Among 32 eligible students and trainees, 29 participants (mean age 26 years; 79% women) were enrolled: 25 (78%) responded to the pre- and 29 (91%) to the post-assessment surveys. Most (80%) were chiropractic students and 20% were postgraduate trainees. Group A consisted of 12 (41%) and Group B of 17 (59%) participants, respectively. We found reasonable feasibility for the new journal club format and our findings were compatible with no difference in before-and-after EBP scores (median EBP total score before: 72.6 [IQR, 63.7–77.4], and after: 73.4 [IQR, 61.3–78.2]). Exploratory subgroup analyses based on journal club attendance were consistent with our overall findings. Conclusion Our study suggests that the newly implemented journal club and embedding chiropractic educational research within the journal club were feasible and acceptable. Small before-and-after differences in the EBP subscale scores for knowledge, attitudes, personal application, and future use were observed in chiropractic students and postgraduate trainees. The small study size and short timeframe during a single semester limit potential inferences.